Which alternative well-fit masks can be used in medical procedures? - Maturin Thapthim-on; Naesinee Chaiear; Thapanawong Mitsungnern (Elsevier, 2024)
Background: During the COVID-19 pandemic, the WHO and CDC recommended that healthcare personnel (HCPs) performing non-aerosol-generating procedures (AGPs) don a properly fitted mask. We aimed to evaluate the fit factors (FFs) of eight alternative well-fit masks (AWMs) used by Thai HCPs. Methods: This comparative descriptive study was conducted on 33 HCPs between October and November 2022, categorized into three facial sizes: small, medium, and large. Each participant wore eight types of AWMs in random order: medical mask under adjustable ear-loop (AEL)-KF94 (MK), medical mask under AEL-KN95 with a hook (MN), medical mask under fabric mask (MF), AEL- KF94 (KF94), AEL-KF94 under fabric masks (KF), AEL-KF94 with a hook (KF94H), AEL-KN95 with a hook (KN95), and AEL-KN95 with a hook under fabric mask (NF). FFs were measured using a quantitative fit test. Results: The respective number of HCPs wearing small, medium, and large was 12, 12, and 9, and the mean±SD of face width and length was 132.98 ± 10.49 and 114.92 ± 10.10 mm. The highest respective median of FF was KN95 = 200, NF= 200, MN= 185, and KF94H = 171, and the respective passing fit-test rate was 97%, 84.8%, 63.6%, and 60.6%. There was no difference in FFs between the N95 and KN95 (p=0.72), the N95 and NF (p=0.202), and the three face sizes. Moreover, KF94H pass rates were significantly higher for females compared to males (OR = 13.3; p = 0.001) and for small facial sizes compared to either medium or large sizes (OR = 14.7; p = 0.009). Conclusion: The AEL-KN95 with hook and sponge at the nosepiece is an effective respirator for use by HCPs in non-AGPs, as the FF and fit test pass rates were comparable to those of N95, and there were no differences in FFs between facial sizes. However, the female who had a small face size may use a KF94H as an alternative PPE.